Change in textural properties, starch digestibility, and aroma of nonfried instant noodles by substitution of konjac glucomannan. Issue 4 (11th June 2019) - Park, Eun Young; Kim, Hyo Yeong; Shin, Hye‐Young; Jeon, Young‐Il; Kim, Jae‐Min; Kim, Semiga; Kim, Jong‐Yea
Abstract: Background and objectives: The physicochemical properties, starch digestibility, and aroma profile of nonfried instant noodles with various glucomannan contents (0%, 0.5%, 1%, and 2%) were investigated to evaluate the effects of glucomannan on overall quality. Findings: The substitution of glucomannan did not induce significant changes in the cooking properties (such as cooking loss and rehydration) and microstructure of the nonfried instant noodles relative to those of the control. The springiness, gumminess, tensile strength, and adhesiveness of the cooked noodles were not significantly changed by the substitution of glucomannan, while the hardness of cooked noodles decreased from 2, 726 to 1, 850 g as the level of glucomannan increased. For in vitro starch digestive properties, the resistant starch content of noodles increased from 1.61% to 4.57% as the level of glucomannan increased. Electronic nose analysis revealed that the substitution of glucomannan altered the aroma profile of nonfried instant noodle compared with that of the control and commercial konjac noodles. Conclusions: The substitution of glucomannan influenced texture (especially, hardness), aroma, and starch digestibility of nonfried instant noodles. Significance and novelty: The substitution of glucomannan in nonfried instant noodles can be effective approach to improve the textural properties and health‐promoting benefit of nonfried instant noodles.